STUDENTS’ ACCEPTANCE OF THE USE OF GOOGLE CLASSROOM AS A PLATFORM IN BLENDED LEARNING - Aulia Khairani; Afrianto Daud; Mahdum Adnan (AL-ISHLAH: Jurnal Pendidikan, 2020)
This study aims to identify the students’ acceptance level of the use of Google Classroom as a platform in Blended-learning and to compare the results between three departments of Language and Arts Department in FKIP of Universitas Riau. Data of this survey research were collected through an online survey using Google form and analysed descriptively. The survey was distributed to all students and 205 of them responded the survey coming from three departments: English Language and Arts Department, Indonesian Language and Arts Department, and Japanese Language and Arts Department in FKIP of Universitas Riau. The questionnaires in the survey used Technology Acceptance Model (TAM) proposed by Davis (1986) with four indicators to measure the students’ acceptance: Perceived Usefulness (PU), Perceived Ease of Use (PEU),  Behavioral Intention (BI), and Actual System Use (AU).   The students’ acceptance levels in terms of  Perceived usefulness (62,8%) was in very good category; Perceived Ease of Use (67,2%) was in very good category; Behavioral Intention (69%) was in very good category; and Actual System Use (48,55%) was  good category. The result shows that the level of the students’ acceptance of Google Classroom, in general, is Very Good (62%). It means, the students positively accepted Google Classroom as a platform in blended-learning. Behavioral Intention was the indicator with the highest percentage (69%) which explains that students are interested and intend to increase their use of the Google Classroom. Data also shows that out of the three departments, English Language and Arts Department has the highest average mean score (3.67) followed by Indonesian Language and Arts Department (3.57) and Japanese Language and Arts Department (3.54). This study implies that English department students experienced more acceptance in using the Google Classroom compared to the other two departments.